Perancangan Dan Penerapan Sıstem Pencatatan Akuntansı Berbasıs Web Pada PT Ashmı Sınar Dynatama - Michael Michael; Daniel Herman (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
MSMEs or commonly known as micro, small and medium enterprises play an important role in the country’s economic growth. But there are still many MSMEs doing their business record manually. This community service (PkM) exist to provide support to one of the MSMEs, PT. Ashmi Sinar Dynamata in recording its business processes. By the use of waterfall method in form of define requirements, design, build, testing to implementation to assist the system creation process. The result of this research is a web-based accounting record system. The recording of business processes in this MSMEs will be a lot faster and more accurate with this system.